2017
DOI: 10.15640/jfbm.v5n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Banks� Profitability in Nigeria: Does Relative Market Power Matter?

Abstract: Purpose -This study investigates the determinants of banks' profitability in Nigeria using a panel dataset between 2001 and 2015.The results of previous empirical studies are mixed and inconclusive in terms of factors that actually influence the level of bank performance as a result of difference in sample period, estimation techniques, and countries. Design/methodology/approach -Ordinary Least Square and Generalized Method of Moment techniques were utilized. Findings -The results show that bank specific facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
1
11
0
5
Order By: Relevance
“…Commercial banks in Nigeria are key and contribute significantly to the economic growth of the country (Akinkunmi, 2017). As financial intermediaries, commercial banks provide variety of services to individuals, corporations and as well as government entities with the ultimate aim of achieving profits (Flamini, McDonald & Schumacher, 2009).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial banks in Nigeria are key and contribute significantly to the economic growth of the country (Akinkunmi, 2017). As financial intermediaries, commercial banks provide variety of services to individuals, corporations and as well as government entities with the ultimate aim of achieving profits (Flamini, McDonald & Schumacher, 2009).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Due to the varying regulatory frameworks and economic conditions of countries, the findings of these studies may not be directly applicable to the Nigerian context. Akinkunmi (2017) studied the variables determining the profitability of banks in the Nigerian context. The study focused on the period 2001 to 2015 while using ordinary least square and GMM.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The macroeconomic factors proxy by GDP and inflation on the other hand have positive insignificant effect. Akinkunmi (2017) found that of all bank-specific measures (capital adequacy, liquidity risks, credit risks and efficiency ratio) employed, only efficiency ratio is a crucial factor that influence profitability of commercial banks in Nigeria. The macroeconomic variables -real GDP growth rate, inflation rate and market concentration however have no significant influence…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Georgesan [14], electronic banking is defined as the provision of retail and small value banking products and services through electronic channels as well as large value electronic payments and other whole sale banking services delivered electronically. In Akinkumi [15] electronic banking enable financial institutions, customers and businesses to access accounts, transact business or obtain information on financial products and services through the internet. Customers access electronic banking services using an intelligent electronic device such as a personal computer (PC) personal digital assistant (PDA), Automated Teller Machine (ATM), among others.…”
Section: Literature Reviewmentioning
confidence: 99%